Cultivating Critical Social Justice Literacy: Surfacing and Examining Candidates' Embodied Knowledge. Issue 1 (3rd April 2022) - Bondy, Elizabeth; Burt, Elizabeth; Bell, Priscilla V.
ABSTRACT: Creating transformative experiences for teacher candidates around issues of critical social justice literacy requires that teacher educators anticipate and prepare for obstacles to learning that arise when knowledge residing in students' bodies is challenged by course content. Scholars have argued that the imprint of students' emotions, experiences, and histories in their bodies–their embodied knowledge–may inhibit their ability to process course content without exploration and interrogation of their embodied response. This article draws from interdisciplinary literature on embodied knowledge and its role in teaching and learning when social justice is front and center. It also outlines examples of a critical pedagogy of emotion that addresses students' embodied knowledge, a core dimension of cultivating critical social justice literacy.